AB0365 Does vitamin D deficiency contribute to infections complicating rheumatoid arthritis?. (23rd January 2014) - Kelly, C.; Aiken, L.; Rizzo, S.; Lumsley, G.
Abstract : Background: Vitamin D levels have been reported as being low in a variety of rheumatological diseases and the possibility that patients who are vitamin D deficient might be at greater risk of developing immunological disease has been raised [1]. Indeed, some studies have suggested an inverse correlation between vitamin D and disease activity in rheumatoid arthritis (RA) [2]. Furthermore, patients with RA are known to have an increased incidence of both acute and chronic infections. Some of the factors contributing to this have been investigated but, to date, there are no data on the possible contribution of low vitamin D levels to this phenomenon. Objectives: To assess the possible contribution of low vitamin D levels to the observed increased risk of infections in patients with RA Methods: We identified 33 patients with RA and recurrent urinary tract infections (UTI), and a further 33 patients with bronchiectasis complicating RA. Patients with UTI had proven urinary pathogens cultured from mid stream urine. Those with bronchiectasis had confirmation of the diagnosis by high resolution computed tomography. We then identified an age and gender matched case control with RA, but no history of bacterial infection within 5 years, for each index patient. These controls were recruited randomly from consecutive out patients with RA. We then measured 1, 25 dihydroxy vitamin D levels in all index cases and case controls in a two month period over the early winter using the same technique. Results were analysed and compared using Students t test after normal distribution of results was confirmed. Results: Our index cases comprised 66 patients with a mean age of 67 (range 43-88 years). As expected, there were a preponderance of females with a female to male ratio of 3.8: 1. Case controls therefore mirrored these data. The mean vitamin D value in RA patients with UTI was 48.0 nmol (SE 7.8), while those with bronchiectasis had a mean vitamin D level of 50.9 nmol (SE 7.2). Among these 66 index RA patients with infection, 7% were vitamin D deficient (<20nmol), 50% were vitamin D insufficient (20-48 nmol) and 43% were vitamin D replete (>48 nmol). By comparison, the mean vitamin D level in the RA case controls was 55.0 nmol (SE 6.3), and 14% were vitamin D deficient, 33% insufficient and 53% replete. There were no significant differences in vitamin D levels between index cases and controls in any comparison. Conclusions: Although persuasive data exist to support the observed increase in risk of infection in patients with RA, and mechanisms to reduce this trend have been suggested [3], the data presented here show no significant contribution of low vitamin D levels to this process. RA patients with acute or chronic infection appear no more likely than RA patients with no history of recent infection to have any evidence of vitamin D deficiency or insufficiency. References: Marques CD, Dantas AT, Fragoso TS, Duarte AL. The importance of vitamin D levels in autoimmune diseases. Rev Bras Rheumatol. 2010; 50: 67-80 Rossini M. Vitamin D deficiency in rheumatoid arthritis: prevalence, determinants and associations with disease activity and disability. Arthritis Research & Therapy 2010; 12: 216-9 Housden M, Bell G, Hamilton J, Heycock C, Saravanan V and Kelly CA. How to reduce morbidity and mortality from chest infections in rheumatoid arthritis. Clinical Medicine 2010, 4: 326-9 Disclosure of Interest: None Declared